Downstream performance analysis and optimization of the next generation passive optical network stage 2 (NG-PON2). (August 2018) - Kachhatiya, Vivek; Prince, Shanthi
Graphical abstract: Highlights: Fiber nonlinearities and reared dispersion are minimized by optimizing launch power. Optimum launch power is evaluated for conventional NRZ-EM and simple RZ-EM formats. The ITU-T G.652A, G.652B and G.655 fiber specifications are used in the simulation. Only at the optimum launch power the performance of a system is maximum. G.655 standard fibers are proposed for future deployment of the NG-PON2. Abstract: The increase in the number of users and high end to end demand of massive data-rate directs the attention towards innovative point to multipoint links that satisfy the need for next-generation passive optical network stage 2 (NG-PON2). NG-PON2 architecture has the capability to support power-split and wavelength-split optical distribution network (ODN) as well as a hybrid of two ODNs. Wavelength routing (WR) ODN has adequate low insertion loss than the power splitter (PS) ODN which can fulfill the exponential increase in demand for greater connectivity. The wavelength routing passive optical network (WR-PON) is investigated using the OptiSystem-13 simulation design tool. In this paper, we optimize the downstream transmission of eight channels WR-PON over 60 km and 40 km of standard single mode practical fibers (G.655 and G.652) with 10 Gb/s per channel and compared it with PS-ODN based passive optical network (PON). Both WR-PON and PS-PON are analyzed in detail under the specifications of deployed optical fibers like ITU-T G.652.A fiber, ITU-T G.652.B fiber, Alcatel 6912 Tealight Ultra 1625 fiber, Corning LEAF 1625 fiber, and Lucent True-Wave RS 1625 fiber. Next generation multi-wavelength system performance is limited predominantly due to fiber dispersion and nonlinearities. Fiber nonlinearities and dispersions are mitigated and performance is enhanced by characterizing the system and optimizing optical launch power for both WR-PON and PS-PON. Furthermore, the effect of optical launch power on performance is investigated and evaluated for each practical fiber configuration with common optical modulation formats, return to zero external modulation (RZ-EM) and non-return to zero external modulation (NRZ-EM). Power budget for each configuration is calculated and tabulated.